2023
DOI: 10.37433/aad.v4i1.269
|View full text |Cite
|
Sign up to set email alerts
|

GMO or GM No? Segmenting a consumer audience to examine their perceptions of genetically modified products

Abstract: The purpose of this study was to examine [State] consumers’ perceptions related to GM products, and how those perceptions and preferences differ based on consumers’ characteristics. Survey respondents held overall neutral but slightly negative perceptions of GM products. While they agreed GM products can help increase food production, they also expressed perceptions that GM products can cause illnesses such as cancer, autism, allergies, and gluten intolerance. Respondents also expressed beliefs that GM product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…The use of both traditional and social media has been beneficial to the food value chain, as farmers can access information through various platforms such as the Internet, radio, television, and mobile phones (Ceccarelli et al, 2022). However, the spread of misinformation through social and online media (Gibson et al, 2022;Rampold et al, 2023) and the risks of eroding trust in digitally mediated relationships (Rijswijk et al, 2023) have caused harm and offset some of the benefits gained by the digitalization of the agricultural sector. New studies have revealed that social media platforms can be useful for sharing agricultural and foodrelated knowledge.…”
Section: Incorporate Media Literacy Education Into Farmer Field Schoo...mentioning
confidence: 99%
“…The use of both traditional and social media has been beneficial to the food value chain, as farmers can access information through various platforms such as the Internet, radio, television, and mobile phones (Ceccarelli et al, 2022). However, the spread of misinformation through social and online media (Gibson et al, 2022;Rampold et al, 2023) and the risks of eroding trust in digitally mediated relationships (Rijswijk et al, 2023) have caused harm and offset some of the benefits gained by the digitalization of the agricultural sector. New studies have revealed that social media platforms can be useful for sharing agricultural and foodrelated knowledge.…”
Section: Incorporate Media Literacy Education Into Farmer Field Schoo...mentioning
confidence: 99%